The Spiral of Violence: A Critical Analysis of The Genealogy of Islamophobia - Mohammad Fuyudun Niam Imam; Fawes Samudra; Muhammad Solahudin (An-Nur International Journal of Islamic Thought, 2023)
The rise of terrorism by extremist groups with religious backgrounds and the development of Islamophobia in the West after 9/11 are essential issues that need to be addressed. After the WTC incident in 2001, the US declared a "war on terror," which has implications for the bad sentiment of Western society towards Islam, which has led to many acts of discrimination and violence against Muslims in the West. There are still few studies that analyze the relationship between religious fundamentalism-extremism and the development of Islamophobia in the West. This study uses a qualitative approach with secondary data analysis from various sources related to the topic discussed.   It was found that propaganda and hateful rhetoric, as well as acts of violence by extremist Muslim groups, helped trigger and strengthen Islamophobia in the West. From the perspective of the spiral of violence theory, the 9/11 terrorist act also gave birth to other violence in the form of military attacks and discrimination against Muslims. Acts of terrorism by Muslim fundamentalists and Islamophobia in the West influence each other in an ongoing cycle of violence. Efforts to prevent terrorism and deradicalization, as well as religious tolerance education, are needed to break this cycle of violence. We recommend further research with a quantitative approach to empirically analyze the impact of acts of terrorism on incidents of Islamophobia.